Makna Sosial dan Fungsi Musik Tagonggong pada Tradisi Tulude Masyarakat Sangihe - Feby Thalia Muliku; La Ode Karlan; Trubus Semiaji; Mimy Astuty Pulukadang; Rahmawati Ohi (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study is motivated by the position of traditional music as a cultural element that not only functions aesthetically but also plays an important role in constructing social meaning, symbolism, and collective identity within a community. This article aims to examine the social meaning and function of Tagonggong music in the Tulude tradition of the Sangihe community in Londoun Village as a diaspora community. The research uses a qualitative method with a cultural ethnographic approach through participatory observation, unstructured interviews with traditional elders, Tagonggong players, and community leaders, as well as documentation. Data analysis was conducted descriptively and interpretatively using Alan P. Merriam's theoretical framework on the function of music. The results of the study show that Tagonggong music has a multidimensional function in the Tulude tradition, including symbolic communication, emotional expression, representation of cultural identity, reinforcement of social norms, and social integration and cohesion within the community.Tagonggong not only functions as an accompaniment to ceremonies, but also as a sacred musical instrument that connects the relationship between humans, ancestors, and God, while also marking the space and time of the ceremony. This finding confirms that Tagonggong is a living cultural archive that preserves the collective memory and ethnic identity of the Sangihe community in exile. Implicitly, this research enriches Indonesian ethnomusicology studies by positioning traditional music as an active social text in maintaining the cultural structure and solidarity of the communities that support it.